(untitled) (Scientific journal of the Fergana State University, 2025)
The article presents the chemical elemental composition of irrigated meadow sas and light gray soils formed in the Fergana region. Also, the concentration clarke, Clarke distribution and radial distribution coefficients of lanthanides and radioactive elements in irrigated meadow-saz soils were developed. At the same time, correlations were revealed between lanthanides and radioactive elements.